2007
DOI: 10.1371/journal.pgen.0030094
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Cell- and Gene-Specific Transcriptional Regulation by the Glucocorticoid Receptor

Abstract: The glucocorticoid receptor (GR) associates with glucocorticoid response elements (GREs) and regulates selective gene transcription in a cell-specific manner. Native GREs are typically thought to be composite elements that recruit GR as well as other regulatory factors into functional complexes. We assessed whether GR occupancy is commonly a limiting determinant of GRE function as well as the extent to which core GR binding sequences and GRE architecture are conserved at functional loci. We surveyed 100-kb reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
271
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 273 publications
(304 citation statements)
references
References 60 publications
29
271
1
1
Order By: Relevance
“…In general, we were struck by the remarkable degree of cell and gene specificity inherent in androgen regulation, as 182 (89%) of the 205 ARGs we identified were apparently androgen-unresponsive in LNCaP cells (DePrimo et al 2002;Nelson et al 2002). Similarly, comparisons of glucocorticoid-responsive genes in different cell types (Rogatsky et al 2003;Wang et al 2004;Phuc Le et al 2005;So et al 2007) revealed little overlap. It will be important in future work to assemble expression and response data from multiple androgen-responsive cell types to better define and understand tissue-specific transcriptional networks radiating outward from AR.…”
Section: Figure 6 Distribution Analysis Of Ares Located Near Args (A)mentioning
confidence: 94%
See 2 more Smart Citations
“…In general, we were struck by the remarkable degree of cell and gene specificity inherent in androgen regulation, as 182 (89%) of the 205 ARGs we identified were apparently androgen-unresponsive in LNCaP cells (DePrimo et al 2002;Nelson et al 2002). Similarly, comparisons of glucocorticoid-responsive genes in different cell types (Rogatsky et al 2003;Wang et al 2004;Phuc Le et al 2005;So et al 2007) revealed little overlap. It will be important in future work to assemble expression and response data from multiple androgen-responsive cell types to better define and understand tissue-specific transcriptional networks radiating outward from AR.…”
Section: Figure 6 Distribution Analysis Of Ares Located Near Args (A)mentioning
confidence: 94%
“…We interrogated ∼104 kb genomic regions centered on the transcription start sites of 548 candidate hormone-responsive genes to identify AREs and to determine the distribution of AREs at promoter proximal, distal, and intragenic regions. These human candidate genes included our 157 putative and validated ARGs identified in HPr-1AR cells, 241 putative and validated glucocorticoid receptor-(GR) responsive genes identified in A549 lung adenocarcinoma cells and U2OS-GR osteosarcoma cells (Rogatsky et al 2003;Wang et al 2004;So et al 2007), and 150 genes potentially hormone-responsive in other cell types (e.g., 35 ARGs from LNCaP cells; DePrimo et al 2002;Nelson et al 2002). GR, which is closely related to AR, binds in vitro with similar affinity as AR to consensus sequences in the elementary halfsites GGTACAnnnTGTTCT (Claessens et al 2001).…”
Section: Identification Of Ar Binding Regionsmentioning
confidence: 99%
See 1 more Smart Citation
“…GRs can bind to DNA as heterodimers with many other transcription factors, such as members of the signal transducer and activator of transcription (STAT) family, the ETS transcription factors and the vitamin D3 receptor [5,6] leading to the recruitment of distinct coactivator (e.g. GRIP-1) or corepressor (e.g.…”
Section: Molecular Mechanisms Of Corticosteroidsmentioning
confidence: 99%
“…(32)(33)(34)(35)(36) A comprehensive review of the mechanisms known for non-Mendelian inheritance is provided by Heyningen and Yeyati (1) and Zlotogora. (2) The factors that affect gene product levels include genespecific transcription (37,38) and translation regulators. (39) Therefore, a monogenic disease could be under the influence of gene-specific interacting partners that are referred to as modifier genes.…”
Section: Molecular Basis Of Ip-vementioning
confidence: 99%